Peningkatan Pengetahuan Manajemen Keuangan Siswa Sekolah Indonesia Jeddah - Wicaksono, Hafizh Mahendra; Rafsanjani, Maulana; Uthana, Ira Fitri; Mahdia, Puan Fitri; Madina, Assayyidah Aisyah; Putra, Yunis Eka; Hanggara, Aditya Dwi; Widodo, Aris Slamet (Universitas Muhammadiyah Yogyakarta, 2025)
Financial literacy is a crucial life skill, especially for Indonesian diaspora children at the Indonesian School in Jeddah (SIJ), Jeddah, Saudi Arabia, most of whom come from families of Indonesian Migrant Workers (PMI) with limited income. PMI families face economic challenges such as delayed wages, financial uncertainty, and social risks, which worsen their financial stability. The low financial literacy of SIJ students, exacerbated by the lack of financial education from families and schools, results in poor money management patterns. Research shows that financial habits are formed from the age of 7, while parental financial literacy plays a significant role in planning for children's education funds. Data from OJK and BPS recorded the national financial literacy index at only 65.43%, with lower figures among students (56.42%) and teenagers aged 15-17 years (51.70%), emphasizing the need for early educational intervention. The International Community Service Program at SIJ is designed to enhance students' understanding of saving and financial management through an engaging interactive approach. The method includes a one-day (3-hour) socialization on